Local Human Capital Externalities: An Overlapping Generation Model and Some Evidence on Experience Premia - Giovanni Peri (Center for Economic Studies and ifo Institute (CESifo), 1999)
In an interesting and influential paper Robert Lucas (1993) considering the experience of East Asian small economies, suggests that 'on the job' learning could be the principal engine of their miraculous growth in the last 20 years. In this paper I develop an overlapping generation model where on the job learning, via local spillovers and local interactions, is the main channel of human capital accumulation in small open economies (as cities). The model predicts that skills' accumulation, due to experience in the local environment, has an effect on the experience premia of the workers and on the dispersion of their wages. I find the balanced growth path of the model and I simulate the adj ustment path after a technological shock. The second part of the paper conveys some suggestive evidence on what local characteristics affect the accumulation of skills, using data from 236 U.S. cities. Local characteristics which seem to have a strong imp act on the accumulation of skills are the dblquote technological intensity dblquote of the local manufacturing sector, the average level of education and the density of teachers in the city. This seems to confirm that the 'quality' of local environments is very important for skills' accumulation.
Keywords: 330